"Delectable North Wales" and Stakeholders: The London & North Western Railway's Marketing of North Wales, c.1904–1914. (28th December 2018) - TURNER, DAVID A.
Abstract : This article discusses the London & North Western Railway's (LNWR) marketing activities before 1914. It extends our understanding of British railway marketing by examining how the company forged links with stakeholders in North Wales, particularly the resort authorities, in support of its development of the tourist trade there. While the company remained the dominant force in promoting the region, cooperative working facilitated the sharing of market intelligence, exchange of best practice, coordination of advertising efforts, coordination of services, and the harmonizing of a promotional message that appealed to middle-class discretionary travelers that North Wales was a place for health and pleasure. The article also shows how the LNWR deployed a system of integrated marketing communications, providing one of the earliest known examples within British business of such practice. The sum result was positive impacts on the development of the North Welsh tourist trade in the years before the World War I.